INFORMATION ARCHITECTURE FOR BUSINESS PROCESS: a way to data governance - Brandt, Mariana Baptista [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (Univ Federal Campina Grande, 2020)
Organizations produce and consume data and information daily in their business processes. Data is produced, fed, consulted, analyzed, and transformed throughout the activities and operations, and is an essential source of information for the development of institutions. The business processes are present in all the activities of the organizations, even if not formalized. Institutions in their various sectors such as finance, human resources, general services, management, and information technology have routines, processes, and tasks that are called business processes. This investigation is based on the following question: how to manage this data properly in a business process for data governance? For governance to be implemented it is necessary a structure in which the data are mapped, organized, documented, and managed. In this context, Information Architecture for Business Processes is presented as an Information Architecture methodology that starts from the business process to obtain the most important information of the processes and represents it, through business metadata, which will be registered and described by attributes, configuring information requirements. Thus, it is observed that Information Architecture for Business Processes must be the starting point for the construction of the information systems that support the business to provide inputs for the management of data and information, and data governance, through its deliverables.
Keywords: Information Architecture; Business Processes; Information Architecture for Business Processes; Business Metadata